2020
DOI: 10.51441/biomedica/5-106
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Thalassemia and Its Association with Hepatitis C Infection in Local Population of Pakistan

Abstract: Background and Objective: Thalassemia major or βeta-thalassemia is a hereditary blood disorder, necessitating continuous blood transfusions. Frequent blood transfusions often result in the development of hepatitis, hepatocellular carcinoma, acquired immunodeficiency syndrome (AIDS) and many other infectious diseases. Incidence of infection of viral hepatitis in thalassemia patients is majorly associated with infections in the donor population. The objective of this study was to ascertain the frequency of HCV i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…Elderly (elderly) as many as 12.5% (6 subjects) and the age group of children (children) as much as 8.33% (4 subjects). These results are comparable to the findings of Khan et al 7 and Sharma et al 8 , where they found a 2:1 male-to-female ratio. In that study, a high percentage of males were traumatized and infected, which was attributed to the statement that males were more involved in trauma-risky work and aggressive play.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Elderly (elderly) as many as 12.5% (6 subjects) and the age group of children (children) as much as 8.33% (4 subjects). These results are comparable to the findings of Khan et al 7 and Sharma et al 8 , where they found a 2:1 male-to-female ratio. In that study, a high percentage of males were traumatized and infected, which was attributed to the statement that males were more involved in trauma-risky work and aggressive play.…”
Section: Discussionsupporting
confidence: 91%
“…In that study, a high percentage of males were traumatized and infected, which was attributed to the statement that males were more involved in trauma-risky work and aggressive play. 7,8 However, Zaidi For adults, the most common causes of unilateral and bilateral proptosis are thyroid-related eye disease or Graves' ophthalmopathy. In children, orbital cellulitis is the most common cause, whereas bilateral proptosis is most likely due to neuroblastoma and leukemia.…”
Section: Discussionmentioning
confidence: 99%
“…βthalassemia major, was described in 1925 by Cooley and Lee, is a life threatening anemia which is characterized by ineffective erythropoiesis, bone marrow expansion, and increase destruction of defective red blood cells (RBCs) (4,5) . The resultant anemia and other complications can be corrected with repeated regular blood transfusion program (6) ; unfortunately, such blood transfusion program will exert its own problems concerning iron overload (7) . The iron overload may have adverse effects on several organs including heart, liver, endocrine glands, lungs, and kidneys (4,5,8) .…”
Section: Introductionmentioning
confidence: 99%
“…Deferroxamine, an iron chelating agent given by subcutaneous infusion is the standard iron chelating agent used since the late 1960s (6,9,10) . Many researchers studied the different complications that arise from the disease and its treatment; however, there are only a few studies on the effects of thalassemia and deferroxamine on renal functions (7,11) . Renal damage can be attributed to chronic anemia, iron over load and deferroxamine therapy (12) .…”
Section: Introductionmentioning
confidence: 99%